Following the trail of crumbs: A bibliometric study on consumer behavior in the Food Science and Technology field - Marcia-Gabriela C. Kasemodel; Fausto Makishi; Roberta C. Souza; Vivian-Lara Silva (International Journal of Food Studies)
The main goal of this paper was to conduct an exploratory study regarding consumer preference in the field of Food Science and Technology. Two questions guided this study: Is it possible to identify a trail of crumbs concerning consumer behavior in the Food Science and Technology field? And, if that trail exists, where is it leading academia in terms of research trends of interest? A bibliometric study was conducted using an analysis software called CiteSpace. The use of this methodology ensured the impartiality of the literature review of the topic of interest. A survey of all articles indexed in Web of Science between 1993 and 2013 regarding consumer behaviour was carried out. In total, 1,786 articles were analyzed. The recent increased concern regarding consumer behavior was evident. With the USA and Spain having a significant role in driving the trail. Eight other countries that exhibited similar influences are: Italy, England, Australia, Germany, Denmark, France, Netherlands and Brazil. The research trends observed were grouped into seven major hot topics: sensory, health, safety, willingness to pay, packaging, ethics, and lifestyle/convenience. However, the development of publishing trends depended on where the research was carried out. A final suggestive finding, demonstrated that scientific knowledge does not occur in a vacuum.